Environmental Accounting Information Disclosure Quality Evaluation of Listed Steel Companies - Zhang, Kai (Transactions on Economics, Business and Management Research, 2024)
Building an environmentally friendly society is one of the important directions of China’s development. The development of enterprises should follow the pace of the country, and every enterprise should do a good job in environmental accounting information disclosure. However, in China’s development over the past years, the importance that enterprises attach to the environment has not improved significantly, and China’s environmental accounting system is still not perfect enough. There is still a long way to go for environmental protection. Taking steel enterprises as an example, this paper analyzes the current situation of environmental accounting information disclosure, summarizes the related problems, and proposes countermeasures on how to improve the quality of environmental accounting information disclosure.